UMUMTA’LIM MAKTABLARIDA YOZMA ISHLARNI TEKSHIRISHGA QO‘YILADIGAN TALABLAR VA UNI TASHKIL ETISH MASALALARI - Hazratqulov, M. (SCIENCE and SOCIETY, 2024)
This article describes the organization of written work in secondary schools and the requirements for examination. At the moment when there are a number of changes related to the assessment of students’ knowledge are presented necessary necessary conclusions and recommendations.